2009
DOI: 10.1103/physrevstper.5.010105
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the force and motion conceptual evaluation and the force concept inventory

Abstract: In this paper we compare and contrast student’s pretest/post-test performance on the Halloun-Hestenes force concept inventory (FCI) to the Thornton-Sokoloff force and motion conceptual evaluation (FMCE). Both tests are multiple-choice assessment instruments whose results are used to characterize how well a first term, introductory physics course promotes conceptual understanding. However, the two exams have slightly different content domains, as well as different representational formats; hence, one exam or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 11 publications
8
94
0
3
Order By: Relevance
“…However, we expect that our results can be extrapolated because they are consistent with the results of the interviews with students at Tokyo Gakugei University, Nagoya University, and Meijo University. Further, Thornton et al and Scott et al found similar results for Q.16 [13,14].…”
Section: Range Of Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…However, we expect that our results can be extrapolated because they are consistent with the results of the interviews with students at Tokyo Gakugei University, Nagoya University, and Meijo University. Further, Thornton et al and Scott et al found similar results for Q.16 [13,14].…”
Section: Range Of Resultssupporting
confidence: 65%
“…Similar shortcomings have been highlighted by other studies. For example, Thornton and colleagues used the interview method to highlight the inadequacy of Q.37 in force and motion concept evaluation [13], and Scott and colleagues performed a factor analysis on an FCI data set and hypothesized why students who answer Q.16 correctly treat it as a question pertaining to Newton's first law rather than to his third law [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in think-aloud studentinterviews, Thornton et al showed that some students chose a correct FCI response using incorrect reasoning. 10 In a previous study using latent Markov chain modeling, 18 we found statistical evidence of the same false-positive (FCI question 16) reported in the qualitative analysis in Ref. 10.…”
Section: Probability Model For Transitionsmentioning
confidence: 71%
“…A reasonably high correlation of r ¼ 0.78 was found, indicating that the score on one instrument is a good predictor of the score on the other. 10 Internal consistency reliability is measured by correlating the total scores on two distinct halves of a test to establish whether the sub-parts are consistent with each other. Internal consistency reliability assumes that a test measures a unique construct across all test items.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Henderson [44] also examined test-retest reliability between the FCI as a graded posttest and as an ungraded quiz given the following semester; excellent test-retest reliability was measured in a sample of 500 university students. The FCI has also been compared with an alternate test of conceptual knowledge of mechanics, the FMCE [14]; a high correlation of overall test scores, r ¼ 0.78, was demonstrated [51].…”
Section: Reliabilitymentioning
confidence: 99%